ANALISIS MIKROBIOLOGIS TERHADAP KUALITAS DAN KEAMANAN PANGAN PRODUK TERASI MELALUI DETEKSI BAKTERI Escherichia coli DAN Salmonella sp. DI UPTD LABORATORIUM KESEHATAN HEWAN DAN KESEHATAN MASYARAKAT VETERINER SIDOARJO - Listianti, Nindira Cahya; Nurfadilah Puspitasari; Nuris Khumairo; Sri Wardiyah; Hanik Faizah (Program Studi Biologi Fakultas Sains dan Teknologi Universitas Islam Negeri Ar-Raniry Banda Aceh, Indonesia, 2025)
Food safety is a crucial component of the food system, ensuring that food is safe and free from health risks. One traditional food product that requires particular attention regarding food safety is shrimp paste. Shrimp paste is a fermented fishery product made from small shrimp or other fish, characterized by its distinctive aroma and flavor. The types of bacteria that grow during fermentation, the raw materials used, processing techniques, and handling of the final product all significantly impact the quality of shrimp paste. This study aims to analyze the quality and food safety of shrimp paste products through the detection of Escherichia coli and Salmonella sp. at the Sidoarjo Animal and Veterinary Health Laboratory. This study used the Most Probable Number (MPN) method to detect Escherichia coli, and a series of tests covering presumptive, selective, and confirmatory stages to detect the presence of Salmonella sp. Six samples were used in this study, obtained from four different locations. The results showed that all shrimp paste samples did not contain Escherichia coli with a value of <3 MPN/gram, and did not contain Salmonella sp. This was indicated by the absence of colonies on XLD media, indicating that all shrimp paste samples met safety standards SNI 2009. Quantitatively, these findings indicate that all shrimp paste samples had very low to undetectable levels of bacterial contamination, thus meeting microbiological safety standards and being safe for consumption. Keywords: Food safety; microbiological analysis; MPN; Escherichia coli; Salmonella sp.